2023
DOI: 10.3390/cancers15153957
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of CB-103, a First-in-Class Transcriptional Notch Inhibitor, in Preclinical Models of Breast Cancer

Abstract: Background: The efficacy of CB-103 was evaluated in preclinical models of both ER+ and TNBC. Furthermore, the therapeutic efficacy of combining CB-103 with fulvestrant in ER+ BC and paclitaxel in TNBC was determined. Methods: CB-103 was screened in combination with a panel of anti-neoplastic drugs. We evaluated the anti-tumor activity of CB-103 with fulvestrant in ESR1-mutant (Y537S), endocrine-resistant BC xenografts. In the same model, we examined anti-CSC activity in mammosphere formation assays for CB-103 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The second approach relies on the binding inhibition of N1-ICD and its transcriptional complex [43]. The most advanced example in this case is CB-103, a small molecule investigated in Notch-driven cancers [44][45][46]. CB-103 showed good efficacy in NOTCH-mutated solid tumors and an acceptable safety profile in a phase I clinical trial [47].…”
Section: Discussionmentioning
confidence: 99%
“…The second approach relies on the binding inhibition of N1-ICD and its transcriptional complex [43]. The most advanced example in this case is CB-103, a small molecule investigated in Notch-driven cancers [44][45][46]. CB-103 showed good efficacy in NOTCH-mutated solid tumors and an acceptable safety profile in a phase I clinical trial [47].…”
Section: Discussionmentioning
confidence: 99%
“… 554 In preclinical models of endocrine-resistant and TNBC, CB-103, when combined with fulvestrant or PTX, exhibits synergistic effects, effectively inhibiting the formation of breast spheroids. 555 Moellering et al introduced a hydrocarbon-stapled peptide named SAHM1, which can prevent the assembly of active transcription complexes. 556 In vivo and in vitro experiments have demonstrated that SAHM1 can treat T-ALL cells by globally suppressing Notch-activated genes.…”
Section: Ongoing Therapeutic Strategies Targeting Notch Signaling In ...mentioning
confidence: 99%
“…In TNBC and T-ALL xenograft models, limantrafin markedly reduced tumor burden and prolonged survival [359]. Limantrafin in combination with paclitaxel or fulvestrant also potently inhibited mammosphere formation in breast MCF-7 and estrogen receptor positive (ER + ) cells [360]. Moreover, limantrafin synergized with paclitaxel in TNBC HCC1187 xenografts, resulting in reduced tumor growth and delayed tumor recurrence after discontinuation of treatment compared to paclitaxel alone [360].…”
Section: Pharmacologic Inhibitorsmentioning
confidence: 99%
“…Limantrafin in combination with paclitaxel or fulvestrant also potently inhibited mammosphere formation in breast MCF-7 and estrogen receptor positive (ER + ) cells [360]. Moreover, limantrafin synergized with paclitaxel in TNBC HCC1187 xenografts, resulting in reduced tumor growth and delayed tumor recurrence after discontinuation of treatment compared to paclitaxel alone [360]. ZLDI-8 is a novel a disintegrin and metalloproteinase 17 (ADAM-17) inhibitor, which is an enzyme involved in Notch activation and cleavage [361].…”
Section: Pharmacologic Inhibitorsmentioning
confidence: 99%